Comparative efficacy and safety of two insulin aspart formulations (Rapilin and NovoRapid) when combined with metformin, for patients with diabetes mellitus: a multicenter, randomized, open-label, controlled clinical trial. (2nd November 2022) - Yao, Jun; Guo, Xiaohui; Sun, Li; Han, Ping; Lv, Xiaofeng; Zhang, Xiuzhen; Mo, Zhaohui; Yang, Wenying; Zhang, Lihui; Wang, Zhanjian; Zhu, Lvyun; Li, Quanmin; et al.
Abstract: Objective: This phase 3 confirmatory diabetes mellitus treatment study compared the safety and efficacy of Rapilin and NovoRapid insulin asparts in combination with metformin. Methods: This 24-week, open-label, randomized, active-controlled, noninferiority phase 3 confirmatory study conducted across centers in China aimed to enroll patients with type 2 diabetes mellitus and blood sugar glucose inadequately controlled by oral antidiabetic drugs. Randomized patients received subcutaneous mealtime Rapilin or NovoRapid (3:1) injections, with metformin. The primary objectives were to demonstrate noninferiority (margin of 0.4%) in HbA1c change from baseline and compare safety profiles of Rapilin versus NovoRapid after 24 weeks. Secondary outcomes included 2-h postprandial plasma glucose (PPG), fasting plasma glucose (FPG), and patients achieving HbA1c <7.0% and ≤6.5%. Results: 590 patients with type 2 diabetes mellitus were randomized to Rapilin ( n = 441) and NovoRapid ( n = 149) groups. After 24 weeks, the mean HbA1c change from baseline was −2.20% (Rapilin) and −2.32% (NovoRapid); the estimated treatment difference based on least-square means was 0.04% (95% CI: −0.17, 0.26), meeting the noninferiority criteria for Rapilin versus NovoRapid. Comparable improvements were reported for mean 2-hour PPG (6.14 and 6.29 mmol/L), FPG (2.02 and 1.70 mmol/L), and patients with HbA1c <7.0% (52.6% and 51.0%) and ≤6.5% (34.2% and 30.9%), in the Rapilin and NovoRapid groups, respectively, with no significant safety or immunogenicity outcome differences. Conclusions: Rapilin demonstrated non-inferior glycemic control, and matching safety and immunogenicity to NovoRapid in patients with type 2 diabetes mellitus also receiving metformin over 24 weeks. Trial registration: ChiCTR20003129041